Management of Gadget Addiction Through Ayurveda in Pediatric Patient: A Single Case Study: LifeScience-Ayurveda - Gajanan Yewale, Dr Prasad; Rathi, Dr. Renu; Mate, Dr. Swapnali; Dikondwar, Dr. Ankush (International Journal of Life Science and Pharma Research, 2023)
11-year-old male patient brought by relatives in Kaumarbhritya OPD with complaints of spending excessive time on smartphones andcomputers with changes in the patient’s behavior since 1 year. Relatives counseled the patient, but he didn’t change his behavior. Previous Doctorsadvised Cognitive behavioral therapy, but that facility was not available at their place, and the parents could not afford it. Hence they came toAyurveda Hospital. The patient is assessed using the Internet addiction test scale and DSM-V scale for social behavior. The patient is diagnosed as acase of Gadget addiction (internet addiction) with abnormal social behavior. After proper physical examinations, the patient is counseled inexplaining the hazardous effects of excessive use of gadgets; along with this, he is advised daily Suryanamskara, &Dhyana(meditation) as a Yogaintervention. The patient was advised to play outdoor games daily, and his gadgets using time were reduced by systematic order. Parents wereadvised to be patient in family functions and social meetings & to spend time with children. All the training regarding intervention is given in PPTformat to the patient. The patient was asked to perform Suryanamaskara on follow-up days. On the 91st day, the patient was reassessed using theInternet addiction test scale and DSM-V scale for social behavior, which were normal. Gadget addiction is a common behavioral problem inchildren. Online gaming, gambling, excessive web browsing, and social media use are all included under the umbrella term "gadget addiction.". Evenif there is treatment for gadget addiction, people in remote areas may find it inconvenient due to a lack of infrastructure and specialized pediatricpsychologists. Hence, finding an effective and convenient treatment for Gadget addiction is necessary. This study aims to assess the efficacy ofAyurvedic management in Gadget addiction based on Ayurveda Non-pharmacological intervention. Any addiction results from bad decision-makingcapacity and less control over the mind. The intervention in this study, like Yoga, satvavajaya, proves beneficial to the patient.